Unawareness of health insurance expiration status among women of reproductive age in Northern Ghana: implications for achieving universal health coverage - Edmund Wedam Kanmiki; Ayaga A. Bawah; James Akazili; Isaiah Agorinyah; John Koku Awoonor-Williams; James F. Phillips; Kassem M. Kassak (BMC, 2019)
Abstract Background Ghana implemented a national health insurance scheme in 2005 to promote the provision of accessible, affordable, and equitable healthcare by eliminating service user fees. Termed the National Health Insurance Scheme (NHIS), its active enrollment has remained low despite a decade of program implementation. This study assesses factors explaining this problem by examining the correlates of insurance status unawareness among women of reproductive age. Methods In 2015, a random probability cross-sectional survey of 5914 reproductive-aged women was compiled in the Upper East Region, an impoverished and remote region in Northern Ghana. During the survey, two questions related to the NHIS were asked: "Have you ever registered with the NHIS?" and "Do you currently have a valid NHIS card?" If the answer to the second question was yes, the respondents were requested to show their insurance card, thereby enabling interviewers to determine if the NHIS requirement of annual renewal had been met. Results are based on the tabulation of the prevalence of unawareness status, tests of bivariate associations, and multivariate estimation of regression adjusted effects. Results Of the 5914 respondents, 3614 (61.1%) who reported that they were actively enrolled in the NHIS could produce their insurance cards upon request. Of these respondents, 1243 (34.4%) had expired cards. Factors that significantly predicted unawareness of card expiration were occupation, district of residence, and socio-economic status. Relative to other occupational categories, farmers were the most likely to be unaware of their card invalidity. Respondents residing in three of the study districts were less aware of their insurance card validity than the other four study districts. Unawareness was observed to increase monotonically with relative poverty. Conclusion Unawareness of insurance care validity status contributes to low active enrollment in Ghana's NHIS. Educational messages aimed at improving health insurance coverage should include the promotion of annual renewal and also should focus on the information needs of farmers and low socio-economic groups.